Biopolitics in The Implementation of AI SatuSehat as a Tool of Health - Kokoh Prio Utomo; Bintoro Wardiyanto; Tuti Budirahayu (Pusbindiklatren Bappenas, 2025)
This study critically examines Indonesia's SatuSehat digital health platform through Michel Foucault's biopower lens, analyzing how Human-Centered AI reshapes relations of power (as state control through digital surveillance and normalization), trust (as public confidence in data security and ethical use), and justice in service distribution (as equitable access requiring inclusive design and infrastructure) in public administration. Using a qualitative case study methodology, it employs Actor-Network Theory and Critical Discourse Analysis to deconstruct official narratives, map stakeholder networks, and analyze application features as techniques of algorithmic biopower. The research reveals a stark contrast between the government's efficiency narrative and on-ground realities of infrastructure gaps, eroded public trust due to data breaches, and risks of digital exclusion. It concludes that SatuSehat functions as a political instrument extending state surveillance and normalization, necessitating robust data protection, transparency, and inclusive governance to prevent deepened social inequalities.